Changes in Romania’s Foreign Policy from the Perspective of NATO and EU Membership - Agnes Nicolescu (Romanian Journal of European Affairs, 2010)
This article aims to analyze the main changes and factors which have an impact on Romania’s foreign policy agenda, considering the fact that our country is a member state of the European Union and also a NATO member. The goal is therefore to identify the possible changes in the decision-making process as far as Romanian foreign policy is concerned, in the context of its accession to the European Union and the major topics that may involve an adaptation to the European Foreign and Security Policy. Romania’s accession to the European Union involves that domestic foreign policy structures function in the spirit and according to the European norms, which means that certain changes and transformations need to be assumed in order to be able to fulfil the proposed objectives. This also implies a revision and ongoing adaptation of the main topics on the Romanian foreign policy agenda, such as, for instance, the issue of how viable the deployment of Romanian troops in Iraq is and its implications in the long term on our country’s relations with the other EU members as well as with the other allies in NATO, or the conflict in Transnistria. With regard to this matter, it is interesting to point out that this situation has sparked off greater interest among the European audience only over the last few years, as Romania joined the European Union, rendering Brussels more sensitive to this issue which, however, is still far from being properly tackled. This has prompted Romanian decision-makers to consider in a more pragmatic and dynamic manner relations with its Eastern neighbours, through already existing instruments such as the Black Sea strategy and the ones still under elaboration, like the European Danube Strategy.